Electron-Ion Coupling Mechanism to Construct Stable Output Performance Nanogenerator - Yan-Yuan Ba (American Association for the Advancement of Science, 2021)
Recently, triboelectric nanogenerators (TENGs) have been promoted as an effective technique for ambient energy harvesting, given their large power density and high energy conversion efficiency. However, traditional TENGs based on the combination of triboelectrification effect and electrostatic induction have proven susceptible to environmental influence, which intensively restricts their application range. Herein, a new coupling mechanism based on electrostatic induction and ion conduction is proposed to construct flexible stable output performance TENGs (SOP-TENGs). The calcium chloride doped-cellulose nanofibril (CaCl2-CNF) film made of natural carrots was successfully introduced to realize this coupling, resulting from its intrinsic properties as natural nanofibril hydrogel serving as both triboelectric layer and electrode. The coupling of two conductive mechanisms of SOP-TENG was comprehensively investigated through electrical measurements, including the effects of moisture content, relative humidity, and electrode size. In contrast to the conventional hydrogel ionotronic TENGs that require moisture as the carrier for ion transfer and use a hydrogel layer as the electrode, the use of a CaCl2-CNF film (i.e., ion-doped natural hydrogel layer) as a friction layer in the proposed SOP-TENG effectively realizes a superstable electrical output under varying moisture contents and relative humidity due to the compound transfer mechanism of ions and electrons. This new working principle based on the coupling of electrostatic induction and ion conduction opens a wider range of applications for the hydrogel ionotronic TENGs, as the superstable electrical output enables them to be more widely applied in various complex environments to supply energy for low-power electronic devices.